Unleashing leadership potential in unprecedented times: Lessons learned from an evaluation of a virtual cohort-based adaptive leadership program for public health executives - Kellie Hall; Cortni Bardier; Deya Greer; Anna Clayton; Ramona Poblete (Elsevier, 2024)
Objectives: This paper presents the evaluation results from the Adaptive Leadership Academy (ALA), a pilot program aimed at developing executive-level leaders in public and community health. Study design: Mixed methods study. Methods: The evaluation followed the Kirkpatrick Model to assess program participants' satisfaction with the training, knowledge and skill gain, and behavior change. Data were collected beginning in December 2021 through August 2022 from 20 program participants via online surveys and key informant interviews. Results: The findings indicated that ALA helped participants improve their leadership knowledge, skills, and capabilities. In particular, the study highlighted the effectiveness of cohort-based leadership development programs using adaptive leadership as the foundation for the curriculum. Participants found the cohort-based model and synchronous components particularly useful in creating a supportive environment in which to be vulnerable and grow. Conclusions: Overall, the evaluation provided evidence that the ALA pilot enhanced leadership knowledge, skills, and capabilities. The findings support the use of adaptive leadership as a framework for leadership development programs in the public health sector.